Skin Autofluorescence–Indicated Advanced Glycation End Products as Predictors of Cardiovascular and All‐Cause Mortality in High‐Risk Subjects: A Systematic Review and Meta‐analysis - Ivan Cavero‐Redondo; Alba Soriano‐Cano; Celia Álvarez‐Bueno; Pedro G. Cunha; Jose A. Martínez‐Hortelano; Miriam Garrido‐Miguel; Carlos Berlanga‐Macías; Vicente Martínez‐Vizcaíno (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Chronic deposits of advanced glycation end products produced by enzymatic glycation have been suggested as predictors of atherosclerotic‐related disorders. This study aimed to estimate the relationship between advanced glycation end products indicated by skin autofluorescence levels and the risk of cardiovascular and all‐cause mortality based on data from observational studies. Methods and Results We systematically searched Medline, Embase, the Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Reviews, and the Web of Science databases from their inceptions until November 2017 for observational studies addressing the association of advanced glycation end products by skin autofluorescence levels with cardiovascular and all‐cause mortality. The DerSimonian and Laird random‐effects method was used to compute pooled estimates of hazard ratios and their respective 95% confidence intervals for the risk of cardiovascular and all‐cause mortality associated with levels of advanced glycation end products by skin autofluorescence. Ten published studies were included in the systematic review and meta‐analysis. Higher skin autofluorescence levels were significantly associated with a higher pooled risk estimate for cardiovascular mortality (hazard ratio: 2.06; 95% confidence interval, 1.58–2.67), which might not be important to moderate heterogeneity (I2=34.7%; P=0.163), and for all‐cause mortality (hazard ratio: 1.91; 95% confidence interval, 1.42–2.56) with substantial heterogeneity (I2=60.8%; P=0.0.18). Conclusions Our data suggest that skin autofluorescence levels could be considered predictors of all‐cause mortality and cardiovascular mortality in patients at high and very high risk.